PERLINDUNGAN TERHADAP PIHAK KETIGA ATAS KETENTUAN PERMODALAN PERSEROAN TERBATAS (PT) BERDASARKAN PERATURAN PEMERINTAH NOMOR 29 TAHUN 2016 TENTANG PERUBAHAN MODAL DASAR PERSEROAN TERBATAS (PT) (Lex Jurnalica, 2019)
AbstractGoverment Regulation Number 29 of 2016 concerning on Amandement of Authorized Capital In The Limited Liability Company has changed the provision authorized capital in the limited liability company which basically determined the lowest is IDR 50.000.000,- (fifthy milion rupiah) and the nominal changed based on the agreement of each founder. The background of it distortion is that the goverment’s objective to make easier to do business and investment particularly for the beginer entepreneur, thus to respect for the freedom to contract principal. This research is having objective to discover the protection for the third party regarding the amandement of authorized capital in the limited liability company after the implementation Goverment Regulation Number 29 of 2016 concerning on Amandement of Authorized Capital In The Limited Liability Company. This research will using the method of literature reseacrh within juridical normative approach, conducted by elaborating toward the main problem and then giving solution for it problem. Based on the result of this research, discovered that the protection for the third party is being unprotected and also the third party has no legal certainty. Therefore, this necassary to make harmonious among Goverment Regulation Number 29 of 2016 concerning on Amandement Authorized Capital In The Limited Liability Company and Indonesia Law Number 40 of 2007 concerning on Limited Liability Company. Keywords: the third party, limited liability company, authorized capital. AbstrakPeraturan Pemerintah (PP) Nomor 29 tahun 2016 tentang Perubahan Modal Dasar Perseroan Terbatas (PT) telah merubah ketentuan modal dasar PT yang semula ditentukan paling sedikit Rp. 50.000.000,- (lima puluh juta rupiah) menjadi diserahkan sepenuhnya kepada kesepakatan para pendiri. Penyimpangan ini dilatarbelakangi oleh keinginan pemerintah untuk memberikan kemudahan berusaha dan berinvestasi khususnya bagi pengusaha pemula serta penghormatan kepada asas kebebasan berkontrak. Penelitian ini bertujuan untuk mengetahui bagaimana perlindungan terhadap pihak ketiga atas perubahan modal dasar PT setelah dikeluarkannya PP Nomor 29 Tahun 2006 tentang Perubahan Modal Dasar Perseroan Terbatas. Metode penelitian yang akan digunakan adalah dengan penelitian kepustakaan yang bersifat yuridis normatif, dengan melakukan pemaparan atas pokok permasalahan yang ditimbulkan untuk kemudian memberikan solusi atas permasalahan tersebut. Berdasarkan hasil penelitian diketahui bahwa Perlindungan terhadap pihak ketiga menjadi tidak terlindungi dan pihak ketiga tidak memperoleh kepastian hukum. Untuk itu perlu adanya penyelarasan antara PP Nomor 29 Tahun 2006 tentang Modal Dasar Perseroan Terbatas dengan Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas. Kata kunci: pihak ketiga, perseroan terbatas, modal dasar.